To find the sum of p and q, we add the fractions p and q:
p + q = 3/4 + (-11/4)
To add fractions, we need to have a common denominator. The common denominator for 4 and 4 is 4. So we rewrite the fractions with this denominator:
p + q = (3/4) + (-11/4)
Now we can add the numerators:
p + q = (3 + (-11))/4
Simplifying the numerator gives us:
p + q = -8/4
We can further simplify the fraction by dividing both the numerator and the denominator by their greatest common divisor, which in this case is 4:
p + q = (-8/4) ÷ (4/4)
p + q = -8/4 ÷ 1/1
p + q = -2 ÷ 1
Thus, the sum of p and q is -2.
Find the sum of p and q if p=3/4 and q=-11/4. Reduce your answer to lowest terms.
1 answer